Experimental Study on Tsunami Risk Reduction on Coastal Building Fronted by Sea Wall - Sadia Rahman; Shatirah Akib; M.T.R. Khan; S. M. Shirazi (The Scientific World Journal)
This experimental study was conducted to idealize the efficacy of sea wall in controlling the tsunami forces on onshore structures. Different types of sea walls were placed in front of the building model. The tsunami forces and the wave heights were measured with and without the sea wall conditions. Types of sea wall, wall height, and wall positions were varied simultaneously to quantify the force reductions. Maximum of 41% forces was reduced by higher sea wall, positioned closer proximity to the model whereas this reduction was about 27% when the wall height was half of the high wall. Experimental investigations revealed that wall with adequate height and placed closer to the structures enables a satisfactory predictor of the force reduction on onshore structures. Another set of tests were performed with perforated wall placing near the building model. Less construction cost makes the provision of perforated sea wall interesting. The overall results showed that the efficacy of perforated wall is almost similar to solid wall. Hence, it can be efficiently used instead of solid wall. Moreover, overtopped water that is stuck behind the wall is readily gone back to the sea through perforations releasing additional forces on the nearby structures.